2016
DOI: 10.1097/ico.0000000000000742
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Deep Anterior Lamellar Keratoplasty Treating Posterior Stroma–Implicated Herpetic Corneal Opacities

Abstract: Deep anterior lamellar keratoplasty is a viable alternative for the management of HSK-related deep stromal opacity. Although posterior corneal folds can be relieved intraoperatively in some of these cases, folds near Descemet membrane should be left in situ because of the high risk of Descemet membrane perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The conventional surgical procedure for treating HSK‐induced corneal ulcer is penetrating keratoplasty (PKP), but recent studies show an increase deep anterior lamellar keratoplasty (DALK) . A study by Wu et al compared full‐bed deep lamellar keratoplasty with penetrating keratoplasty in treating corneal scarring caused by Herpes Simplex Keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional surgical procedure for treating HSK‐induced corneal ulcer is penetrating keratoplasty (PKP), but recent studies show an increase deep anterior lamellar keratoplasty (DALK) . A study by Wu et al compared full‐bed deep lamellar keratoplasty with penetrating keratoplasty in treating corneal scarring caused by Herpes Simplex Keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding DALK procedure (Table 2), a significant improvement in vision after the operations was described (21,(27)(28)(29). The rejection was lower than 5% in the studies of Ren et al (28) and Wang et al (29) in a 50.4-month and 31-month follow-up period, respectively, while no rejection was detected in a 31-month follow-up period according to…”
Section: Primary Outcomesmentioning
confidence: 92%
“…In the study of Lyall et al (27), increased IOP, bacterial keratitis and graft failure was found in 27.7% of the patients. Several complications including double anterior chamber, corneal endothelial decompensation and posterior stromal folds were described in 10.1%, 3.4% and 46.1% of the population, respectively, in Ren et al (28) records. No recurrence was noted in patients who had DALK procedure using ACT (32).…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…34 DALK which is less invasive surgery is maybe more suitable for refractive stromal keratitis. 35 Any ophthalmic surgery has been associated with recurrence of disease, including routine cataract surgery. 36 There have also been rare cases of spontaneous HK infection after cataract surgery 37 and it is postulated that the use of topical corticosteroids could promote recurrence.…”
Section: Recurrencementioning
confidence: 99%